2011
DOI: 10.1007/s11782-011-0118-3
|View full text |Cite
|
Sign up to set email alerts
|

A study on the key factors influencing international franchisors’ choice of entry modes into China

Abstract: This paper examines factors associated with international franchising firms' entry modes when they enter the Chinese market. To this end, a survey was conducted to investigate the linkage between entry modes and characteristics of franchising firms. The logit model and regression analysis were used to test the hypotheses. Findings reveal four factors that significantly influence international franchisors' entry mode choices including cultural and geographic distance, international market experience, risk sprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Similar conclusions were drawn in a study conducted in China. It has been found that franchise enterprises are predecided to internationalize their business activities through franchising in countries that are geographically and culturally closer to the country of origin of the franchisor (Zhu et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Similar conclusions were drawn in a study conducted in China. It has been found that franchise enterprises are predecided to internationalize their business activities through franchising in countries that are geographically and culturally closer to the country of origin of the franchisor (Zhu et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The international franchising literature identifies two streams of literature on the factors influencing the decision of a franchise to international: macrolevel and microlevel determinants. 2 The macro perspective of international franchising investigates various host country conditions such as culture (Baena and Cerviño 2014;Zhu, Wang, and Quan 2011;Alon 2006;Altinay and Wang 2006;Fladmoe-Lindquist and Jacque 1995;Kedia, Ackerman, and Justis 1995;Eroglu 1992;Huszagh, Huszagh, and McIntyre 1992), political environment (Baena 2012;Alon 2006;Eroglu 1992;Huszagh, Huszagh, and McIntyre 1992), geographic distance (Alon 2006;Baena 2012;Baena and Cerviño 2014;Dant and Grünhagen 2014), economic conditions (Eroglu 1992;Huszagh, Huszagh, and McIntyre 1992;Alon 2006), and legal or regulatory hurdles (Huszagh, Huszagh, and McIntyre 1992;Buchan 2014;Melo, Borini, and Ogasavara 2019) and their impact on international franchising. For example, low economic growth, intense competition, and unpredictable home demand that may decrease domestic profits will increase the propensity for international franchising.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the study generally reviewed literature from developing countries without specifically identifying the major factors affecting the internationalization of small and medium-sized agricultural exporters in Nigeria. Zhu et al (2011) carried out a study on "the key factors influencing international franchisors' choice of entry modes into China". The study used primary data obtained through a questionnaire survey of 130 international franchise firms in China.…”
Section: Empirical Review Of Barriers To Smes Internationalizationmentioning
confidence: 99%